Implications of new technical measures regulation for cetacean bycatch in European waters. (February 2021) - Dolman, S.J.; Evans, P.G.H.; Ritter, F.; Simmonds, M.P.; Swabe, J.
Abstract: For decades, cetacean bycatch has been a major conservation and welfare concern in the European Union with high numbers of harbour porpoises, dolphins and whales dying each year. Despite binding legal requirements to monitor and reduce bycatch, cetacean bycatch monitoring has been insufficient in most fisheries and areas to generate reliable estimates of bycatch rate. Measures to reduce bycatch have been limited and not always directed at the most problematic fisheries. EU cetacean bycatch legislation (Council Regulation (EC) No. 812/2004) was repealed and replaced by a new Regulation, Regulation on the conservation of fishery resources and the protection of marine ecosystems through technical measures (2019/1241) . Whilst some improvements have been made in the new Regulation, scientific advice of the ICES Bycatch Working Group (ICES WGBYC), and other expert regional bodies, such as ASCOBANS and ACCOBAMS, were not incorporated explicitly and some measures in the adopted Technical Measures Regulation weaken both the provisions of the existing cetacean bycatch legislation and the Commission's original proposal. The bycatch measures adopted for cetaceans are not sufficient to mitigate bycatch effectively in European waters. Management solutions to reduce bycatch are identified and a number of general recommendations towards development of national and regional management plans, implementation and enforcement to that end are made. Highlights: Cetacean bycatch is a major conservation and welfare concern in the European Union. Historic regulation is piecemeal and inadequate. New technical measures provide both opportunities and weaknesses. Member States should be compelled to meet the requirements of the law. Enforcement by the European Commission would save many thousands of cetaceans each year.